2021
DOI: 10.1096/fj.202100572r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the HIF‐1α/BNIP3 pathway has a retinal neuroprotective effect

Abstract: Retinal ischemia is a leading cause of irreversible blindness worldwide. Inner retinal dysfunction including loss of retinal ganglion cells is encountered in a number of retinal ischemic disorders. We previously reported administration of two different hypoxia-inducible factor (HIF) inhibitors exerted neuroprotective effects in a murine model of retinal ischemia/reperfusion (I/R) which mimics these disorders, as inner retinal degeneration could be involved in pathological HIF induction. However, this notion ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…With regard to improvements in retinal damage, we found that oral administration of pemafibrate ameliorated the reduction in the amplitudes of the a-wave and b-wave 5 days after retinal I/R injury (Figure 1C,D). Loss of mid-peripheral retinal ganglion cells (observed in our and other previous reports 4,26,47,48 ) was substantially suppressed by the oral administration of pemafibrate 5 days after retinal I/R injury, as analyzed by NeuN staining (Figure 1E,F). We further confirmed that retinal I/R injury-induced retinal cell loss was related to retinal cell death, as analyzed by the TUNEL assay under our current conditions (Figure S2).…”
Section: Oral Administration Of Pemafibrate Prevents Retinal Damages ...supporting
confidence: 81%
See 2 more Smart Citations
“…With regard to improvements in retinal damage, we found that oral administration of pemafibrate ameliorated the reduction in the amplitudes of the a-wave and b-wave 5 days after retinal I/R injury (Figure 1C,D). Loss of mid-peripheral retinal ganglion cells (observed in our and other previous reports 4,26,47,48 ) was substantially suppressed by the oral administration of pemafibrate 5 days after retinal I/R injury, as analyzed by NeuN staining (Figure 1E,F). We further confirmed that retinal I/R injury-induced retinal cell loss was related to retinal cell death, as analyzed by the TUNEL assay under our current conditions (Figure S2).…”
Section: Oral Administration Of Pemafibrate Prevents Retinal Damages ...supporting
confidence: 81%
“…An early response transcription factor c-Jun, a heat shock stress response factor Hsp25, and antioxidant factors (Nrf2 and Hmox-1) were screened based on several previous studies and the public GEO database (Figure S1, and Table S1 and S2). 26,[57][58][59][60][61][62][63] While the expression of c-Jun was remarkably decreased by oral administration of pemafibrate (Figure 3C), the expression levels of Hsp25, Nrf2, and Hmox-1 were considerably increased by oral administration of pemafibrate (Figure 3D,E).…”
Section: Oral Administration Of Pemafibrate Alters Various Retinal Ge...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al, demonstrated that 2-azahypoxanthine (AHX), a fairy chemical from the fungus Lepista sordida [ 44 , 45 ], had an inhibitory effect on HIF activation in retinal cells and suppressed Vegf mRNA upregulation under CoCl 2 -induced pseudo hypoxic conditions [ 46 ]. Moreover, Kunimi et al, reported inhibition of the Hif-1α/Bnip3 pathway has a retinal neuroprotective effect [ 47 , 48 , 49 ]. Although the clinical study using HIF-inhibitors has not been started, a HIF inhibitor becomes available in the future, it would have the advantage of inhibiting VEGF in addition to retinal protection.…”
Section: Potential For Hif Inhibitorsmentioning
confidence: 99%
“…The retinas then were flat-mounted, and the sections were mounted on slide glass. The TUNEL assay was performed based on our previous reports 49,50 .…”
Section: Immunohistochemistrymentioning
confidence: 99%